2020
DOI: 10.1111/jan.14313
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of music therapy for patients with cancer: A systematic review and meta‐analysis

Abstract: Aims To assess the effectiveness of music therapy on the quality of life, anxiety, depression and pain of patients with cancer. Design Systematic review. Data Sources Five electronic databases were searched in September 2018 for randomized controlled trials evaluating music therapy for patients with cancer. Review Methods The quality of the studies was assessed using the risk of bias tool recommended by the Cochrane Handbook Version 5.1.0 and the Revman version 5.3 software was used to perform the meta‐analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 39 publications
2
59
0
7
Order By: Relevance
“…Music therapy is a health discipline that involves using music and conducting musical activities to treat individuals with specific physical, emotional, cognitive, and social needs [26]. Goals in music and medicine in general may be summarized according to the following: [53].…”
Section: Music Erapymentioning
confidence: 99%
See 1 more Smart Citation
“…Music therapy is a health discipline that involves using music and conducting musical activities to treat individuals with specific physical, emotional, cognitive, and social needs [26]. Goals in music and medicine in general may be summarized according to the following: [53].…”
Section: Music Erapymentioning
confidence: 99%
“…Evidence-based use of music therapy is directed to accomplish physical, emotional, cognitive, and social needs of individuals [25]. Even though recent systematic review show that music therapy is the most advantageous for improving quality of life and reducing anxiety, depression, pain, and fatigue in cancer patients [26], there is no systematic review evaluating the effect of music therapy on breast cancer patient group. To the best of our knowledge, this is the first systematic review analysing the effect of music therapy in breast cancer patient group.…”
Section: Introductionmentioning
confidence: 99%
“…10 According to recent systematic review, music therapy seems to be the most effective for elevating QOL and decreasing pain, fatigue, depression and anxiety for cancer patients. 11 Music therapy and art therapy reveal effective opportunities for patients with cancer for reducing negative emotional status and improving QOL. 12 It seems to have promising efficacy for non-medicated therapeutic options.…”
Section: Editorialmentioning
confidence: 99%
“…Some meta-analyses have reported a superior effect of music-based intervention on the decreased anxiety and depression levels in pregnant women, patients with cancer, and patients with surgical operation. [ 11 , 12 ] A recent network meta-analysis by Watt et al [ 13 ] found that music-based intervention was more efficacious than pharmacologic interventions for reducing aggression and agitation in adults with dementia. During the past 10 years, a total of five meta-analyses regarding the therapeutic file://C:\Documents and Settings\Administrator\Local Settings\Application Data\youdao\dict\Application\7.5.2.0\resultui\dict\?keyword = effect of music-based intervention on aggressive behavior were published [ 13 17 ] ; however, no study focused on children and adolescents.…”
Section: Introductionmentioning
confidence: 99%